A Comparative Study of Nerve Growth Factor Level in the Follicular Fluid of Polycystic and Non-Polycystic Ovary Syndrome Women Undergoing ICSI: a Cross-sectional Study - Noor Kareem Alfatlawy 1 , Hanan Abdul Jabbar AL –Taee 2 , Ali Ibrahim Rahim 3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background : Nerve growth factor is a member of a group of proteins called Neurotrophins (NTs), whichare necessary for growth and differentiation of neurons in both central and peripheral nervous systems. Inaddition to this essential role, NGF has been suggested to play a possible role in ovarian functions. Thus, weproposed this study to evaluate the nerve growth factor level in the follicular fluid of women with polycysticovary syndrome undergoing Intracytoplasmic sperm injection (ICSI) in comparison with the control group(non-polycystic women).Results : Follicular fluid nerve growth factor levels of non PCOS women were significantly higher thanthese of PCOS group (245.399 ± 63.41pg/ml vs. 149.592 ± 64.86 pg/ml), p-value =0.0001*. Also, it wassignificantly correlated negatively with oocytes number (Correlation Coefficient r= -0.431, P-value = 0.01)and positively with FSH (r=0.370, p value = 0.029).Conclusion: Nerve growth factor level in the follicular fluid of polycystic ovary syndrome women is lowerthan it in non-PCOS ones. Additionally, it correlates directly with cycle day two FSH and inversely withoocytes number.